Use of Augmented Reality for demonstration of PET/CT and X-ray room to teaching Medical Physics in Nuclear Medicine - Razuck, Fernando Barcellos; Gonçalves, Gabriel de Lima; de Sá, Lídia Vasconcellos (Revista Brasileira de Física Médica, 2020)
One of the great challenges for professionals in Medical Physics (MP) is to manage the fundamentals of radiation protection, aiming at the protection itself, the patient's, the general public and the environment. Thus, the use of techniques that adopt radiological protection is extremely relevant for application and training in the area. In this sense, this paperaims to propose the application of Augmented Reality (AR) methodology as a teaching tool in MP andNuclear Medicine (NM) training, using as an example the PET/CT equipment modeling and an X-ray room. The methodology involved the analysis of the equipment and the environment cited in real size for the modeling in virtual elements, and later creation of devices in the form of QR-codes, where it is possible to visualize the modeling animations. It is understood that the use of the AR tool can aid in equipment and procedurestraining, with emphasis on those that potentially pose a risk ofoccupational exposure to ionizing radiation in NM services. In addition, it can assist in the teaching of terms and concepts, by making learning more dynamic and interactive through the visualization of equipment, meeting the fundamentals advocated by radiation protection, by avoiding, for example, visiting an hospitalenvironment.